Improving early literacy : - Miller, Wilma H. (Jossey-Bass, 2005)
Improving Early Literacy offers teachers an arsenal of reading strategies for helping struggling emergent readers develop letter-name knowledge, sight word knowledge, phonics, and reading fluency skills. This book provides a comprehensive listing of various strategies incorporated into activities and worksheets and offers